Inappropriate crushing information on ward lists: cytotoxic drugs, capsules, and modified release formulations are gravely neglected - Lohmann, Kristina; Ferber, Julia; Send, Alexander Francesco Josef; Haefeli, Walter E.; Seidling, Hanna (European journal of clinical pharmacology, 2014)
The aim of this study was to assess the quality of the information sources on the modification of solid medication dosage forms (crushing, suspending) used on the wards of a large university hospital in Germany.
Gesehen am 10.09.2020